STRATEGI BERTAHAN (SURVIVAL STRATEGY); STUDI TENTANG âAGAMA ADATâ ORANG LOM DI DESA PEJEM, KECAMATAN BELINYU, KABUPATEN BANGKA, PROVINSI KEPULAUAN BANGKA BELITUNG - Sulaiman, Aimie (SOSIOLOGI, 2014)
Lom people are the oldest tribe in Bangka and still maintain and carry out religious practices derived from their ancestral beliefs in daily life. Although at this time the majority of the Lom had converted to Islam, a small portion Christians and Buddhists. Survival strategies that people use their indigenous religion Lom to make this community to the attention of many people to study and conduct research to it. It can be concluded that the values of the belief system Lom contains taboos and rituals that would have a very recognized their significance as a holy and regulations have been passed down from generation to generation. Islam is believed the majority of people only as a symbol Lom and complement their life course, regardless of the pressure caused government requiring them to hold one of the official religions that exist in the Republic of Indonesia. That way they are not said to be a community of atheists, infidels, and primitive. However, due to the dominance of the Lom original belief system is more powerful than the religion of Islam, led to the values of trust is difficult ancestral replaced with the values of other beliefs.Â Keywords : Â Lom, Agama Adat, and Survival Strategy